THE PROFILE OF GURU PENGGERAK (MOVER TEACHER): A LITERATURE REVIEW - Saiful Anwar; Sundari Hamid; Asdar Asdar (Teaching English as a Foreign Language Overseas Journal, 2022)
Guru penggerak education is a leadership education program for teachers to become learning leaders . Guru penggerak education is designed to produce teachers who can become agents of educational transformation. This literature review aims to describe the profile of guru penggerak. This article uses a qualitative approach by conducting a literature review that is relevant to the topic of study. The primary data sources are Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 26 of 2022 and the guru penggerak education module. The secondary data is in the form of books or other relevant literature. Based on the review of the literature, the profile of the guru penggerak is a teacher who has the ability to: (1) plan, implement, assess, and reflect on learning according to the current and future needs of students based on data; (2) collaborate with parents, colleagues, and the community to develop the vision, mission, and education unit programs; (3) develop competencies independently and continuously based on the results of reflection on learning practices; and (4) developing a learning ecosystem through voluntary exercise, voluntary exercise, sports and thought exercise with colleagues and the community.